Thermosensitive PLGA-PEG-PLGA Hydrogel as Depot Matrix for Allergen-Specific Immunotherapy - Sonja Heine; Antonio Aguilar-Pimentel; Dennis Russkamp; Francesca Alessandrini; Valerie Gailus-Durner; Helmut Fuchs; Markus Ollert; Reinhard Bredehorst; Caspar Ohnmacht; Ulrich M. Zissler; Martin Hrabě de Angelis; Carsten B. Schmidt-Weber; et al. (MDPI AG, 2022)
Allergen-specific immunotherapy (AIT) is the only currently available curative treatment option for allergic diseases. AIT often includes depot-forming and immunostimulatory adjuvants, to prolong allergen presentation and to improve therapeutic efficacy. The use of aluminium salts in AIT, which are commonly used as depot-forming adjuvants, is controversially discussed, due to health concerns and Th2-promoting activity. Therefore, there is the need for novel delivery systems in AIT with similar therapeutic efficacy compared to classical AIT strategies. In this study, a triblock copolymer (hydrogel) was assessed as a delivery system for AIT in a murine model of allergic asthma. We show that the hydrogel combines the advantages of both depot function and biodegradability at the same time. We further demonstrate the suitability of hydrogel to release different bioactive compounds in vitro and in vivo. AIT delivered with hydrogel reduces key parameters of allergic inflammation, such as inflammatory cell infiltration, mucus hypersecretion, and allergen-specific IgE, in a comparable manner to standard AIT treatment. Additionally, hydrogel-based AIT is superior in inducing allergen-specific IgG antibodies with potentially protective functions. Taken together, hydrogel represents a promising delivery system for AIT that is able to combine therapeutic allergen administration with the prolonged release of immunomodulators at the same time.